A method for preparing a monolithic catalyst using a supergravity reactor
By performing acid etching pretreatment on the support surface and loading the silica coating in the supergravity reactor, combined with the impregnation method to load the active components, the problem of easy coating of the catalyst in the supergravity reactor is solved, and the catalyst is improved Mechanical properties and lifespan.
Patent Information
- Application Number
- CN202211608210.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-14
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2042-12-14
AI Technical Summary
In supergravity reactors, the coating and active components of the monolithic catalyst are prone to fall off, resulting in low mechanical strength and short life, making it difficult to meet the needs of efficient reactions.
The binding force of the coating to the entire matrix is enhanced by acid etching pretreatment on the support surface and loading the silicon oxide coating in a centrifugal environment in a supergravity reactor, combined with the impregnation method.
It significantly reduces the shedding rate of the coating and active components, improves the specific surface area and mechanical locking performance of the integrated catalyst, and extends its service life.
Smart Images

Figure CN115845872B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalyst preparation, and more specifically, to a method for preparing a monolithic catalyst by using a supergravity reactor. Background Art
[0002] The ultra-gravity reactor is an efficient reactor that generates a centrifugal field through high-speed rotation to enhance mass transfer and micro-mixing. It has been widely used in many fields such as distillation separation, selective absorption, flue gas desulfurization, catalytic hydrogenation, and wastewater treatment. For common catalytic reactions in reactors, since the reaction system is mostly a quasi-homogeneous system, there is a problem that the catalyst and the product are not easy to separate during the reaction process. Compared with traditional granular catalysts, monolithic catalysts in ultra-gravity reactors have shown significant advantages in many reactions. It has many advantages such as reduced bed pressure, high mass transfer efficiency, and easy separation of catalysts and products. The monolithic catalyst consists of one or more of a monolithic matrix, a coating, and an active component. The role of the coating is to expand the surface area of the monolithic matrix and improve the dispersion and adhesion of the active components. It is well known that a solid catalyst with industrial applications must have excellent mechanical properties such as resistance to reaction media, temperature, and erosion in addition to good activity. The rotating packing in the rotor of the supergravity reactor can shear and cut the liquid into tiny droplets, liquid films or liquid lines, which is beneficial to the gas-liquid mass transfer and liquid-solid mass transfer process, and is beneficial to the liquid renewal rate on the solid surface. However, since the liquid is in a highly dispersed, highly turbulent and strongly mixed state, various destructive stresses in the reactor cause the active substances (coatings and active components) to fall off from the surface of the overall inert matrix. Therefore, for the supergravity reactor, good adhesion between the overall catalyst matrix and the coating and the active components is crucial.
[0003] The adhesion of the coating affects the life and efficiency of the monolithic catalyst. At present, the commonly used methods for loading the coating on the surface of the monolithic substrate include impregnation and slurry circulation, which have problems such as easy detachment of the coating and low mechanical strength. By loading the silicon oxide coating in a supergravity reactor under a supergravity environment, the anti-detachment performance is improved in a simpler way, and the loading is more uniform, which expands the application scope of the monolithic catalyst in the supergravity reactor. Summary of the invention
[0004] The first technical problem to be solved by the present invention is to provide a method for preparing a monolithic catalyst using a supergravity reactor. The monolithic catalyst prepared by the preparation method can significantly reduce the shedding rate of the coating and active components.
[0005] In order to solve the above-mentioned first technical problem, the invention adopts the following technical solution:
[0006] A method for preparing a monolithic catalyst using a high gravity reactor comprises the following steps:
[0007] S1. Carrier surface acid etching pretreatment:
[0008] The carrier of the monolithic catalyst is immersed in acetone, alcohol, and deionized water respectively and cleaned with ultrasonic waves, and then the carrier is immersed in HCl solution, taken out and rinsed with deionized water to ensure that the residual solution in the pores is blown clean, dried at room temperature, dried in an oven, and calcined in a muffle furnace; the purpose of this step is to remove oil and impurities on the surface of the carrier and increase the surface roughness of the carrier;
[0009] S2, preparing a coating slurry for forming a coating;
[0010] S3, loading the carrier treated in step S1 into the rotor of the high gravity reactor, passing the coating slurry obtained in step S2 into the high gravity reactor under the high gravity environment, turning on the motor and the centrifugal pump, conveying the coating slurry to the liquid distributor of the high gravity reactor through the centrifugal pump, spraying it into the rotor through the spray hole, returning to the liquid storage tank after passing through the rotor, and circulating the reaction for a period of time; taking out the carrier loaded with the coating, first drying it at room temperature, then drying it in an oven, and finally placing it in a tubular furnace for calcination; obtaining a carrier of a monolithic catalyst with a coating;
[0011] S4, active component loading by impregnation method:
[0012] The coated carrier is immersed in a prepared metal salt solution containing active components and allowed to stand for a period of time to obtain a monolithic catalyst precursor; it is then dried at room temperature, then dried in a vacuum drying oven, and finally placed in a tubular furnace for reduction in a hydrogen environment to obtain a monolithic catalyst.
[0013] Preferably, in step S1, the carrier of the monolithic catalyst comprises one of cordierite, nickel foam, copper foam, aluminum foam or alloy foam.
[0014] Preferably, in step S1, the ultrasonic cleaning is performed 1-3 times; and the deionized water rinsing is performed 3-5 times.
[0015] Preferably, in step S1, the ultrasonic cleaning time is 10-30 min / time; the deionized water rinsing time is 5-10 min / time.
[0016] Preferably, in step S1, the time for soaking the carrier in the HCl solution is 25-35 minutes.
[0017] Preferably, in step S1, the drying time at room temperature is 5-12 hours.
[0018] Preferably, in step S1, the drying temperature in the oven is 30-80°C and the drying time is 2-5h.
[0019] Preferably, in step S1, the calcination temperature in the muffle furnace is 200-700° C., and the calcination time is 1.5-3 h.
[0020] Preferably, in step S1, the concentration of the HCl solution is 0.5-5 mol / L; more preferably, the concentration of the HCl solution is 3-4 mol / L.
[0021] Preferably, in step S2, the coating comprises one of silicon oxide, aluminum oxide, cerium oxide, activated carbon and molecular sieve.
[0022] Preferably, in step S3, the speed of the rotor in the ultragravity reactor is 500-1500 r / min; preferably, in step S3, the cyclic reaction for a period of time refers to a cyclic reaction for 40-60 min.
[0023] Preferably, in step S3, the coated carrier is taken out and dried at room temperature for 10-14 hours; the temperature in the oven is 70-90° C., and the drying time in the oven is 1-3 hours;
[0024] Preferably, in step S3, the calcination temperature in the tube furnace is 450-550°C, the calcination time is 1-3h, and the heating rate is 4-6°C / min.
[0025] Preferably, in step S4, the metal salt solution includes one or more of palladium salts, platinum salts, cobalt salts, nickel salts, copper salts, and iron salts.
[0026] Preferably, in step S4, the standing for a period of time refers to standing for 20-60 minutes.
[0027] Preferably, in step S4, the drying time at room temperature is 10-14 h, and the drying temperature in the vacuum drying oven is 55-65° C. and the drying time is 4-6 h.
[0028] Preferably, in step S4, the temperature in the tube furnace is 380-420°C, the reduction time is 1.5-2.5h, and the heating rate is 1.5-2.5°C / min.
[0029] Any range described in the present invention includes the end value and any numerical value between the end values and any sub-range formed by the end value or any numerical value between the end values.
[0030] Unless otherwise specified, all raw materials in the present invention can be purchased from the market, and the equipment used in the present invention can adopt conventional equipment in the relevant field or refer to the existing technology in the relevant field.
[0031] Compared with the prior art, the present invention has the following beneficial effects: :
[0032] 1. The present invention uses a supergravity reactor to load the coating in a supergravity environment, thereby increasing the uniformity and dispersibility of the coating, and the prepared monolithic catalyst has an increased specific surface area, so that the monolithic catalyst can obtain a larger specific surface area under a smaller loading amount.
[0033] 2. The monolithic catalyst prepared by the present invention has a fast liquid renewal rate on the solid surface in the high-gravity reactor during the preparation process, so that the coating and the overall matrix surface are more tightly combined, which is more conducive to the mechanical locking of the interface. In the anti-shedding test, the shedding rate of the coating and the active component is significantly reduced, which can meet the use requirements in various types of high-gravity reactors. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] The specific embodiments of the present invention will be further described in detail below with reference to the accompanying drawings.
[0035] Figure 1 The schematic diagram of the whole process flow of the monolithic catalyst preparation used in the present invention is shown. DETAILED DESCRIPTION
[0036] In order to more clearly illustrate the present invention, the present invention is further described below in conjunction with preferred embodiments and accompanying drawings. Similar components in the accompanying drawings are represented by the same reference numerals. It should be understood by those skilled in the art that the content specifically described below is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.
[0037] Various cross-sectional views of the embodiments disclosed in the present invention are shown in the accompanying drawings. These drawings are not drawn to scale, and some details are magnified and some details may be omitted for the purpose of clear expression. The shapes of various regions and layers shown in the drawings and the relative sizes and positional relationships between them are only exemplary, and may deviate in practice due to manufacturing tolerances or technical limitations, and those skilled in the art may design regions / layers with different shapes, sizes, and relative positions according to actual needs.
[0038] At present, for the ultra-gravity reactor, good adhesion between the monolithic catalyst matrix and the coating and the active components is crucial. The adhesion of the coating affects the life and efficiency of the monolithic catalyst. At present, the commonly used methods for loading the coating on the surface of the monolithic matrix include impregnation method, slurry circulation method, etc., which have problems such as easy detachment of the coating and low mechanical strength.
[0039] Based on this, see Figure 1 As shown, as one aspect of the present invention, the present invention provides a method for preparing a monolithic catalyst using a supergravity reactor, comprising the following steps:
[0040] S1. Carrier surface acid etching pretreatment:
[0041] The carrier of the monolithic catalyst is immersed in acetone, alcohol, and deionized water respectively and cleaned with ultrasonic waves, and then the carrier is immersed in HCl solution, taken out and rinsed with deionized water to ensure that the residual solution in the pores is blown clean, dried at room temperature, dried in an oven, and calcined in a muffle furnace; the purpose of this step is to remove oil and impurities on the surface of the carrier and increase the surface roughness of the carrier;
[0042] S2, preparing a coating slurry for forming a coating;
[0043] S3, loading the carrier treated in step S1 into the rotor of the high gravity reactor, passing the coating slurry obtained in step S2 into the high gravity reactor under the high gravity environment, turning on the motor and the centrifugal pump, conveying the coating slurry to the liquid distributor of the high gravity reactor through the centrifugal pump, spraying it into the rotor through the spray hole, returning to the liquid storage tank after passing through the rotor, and circulating the reaction for a period of time; taking out the carrier loaded with the coating, first drying it at room temperature, then drying it in an oven, and finally placing it in a tubular furnace for calcination; obtaining a carrier of a monolithic catalyst with a coating;
[0044] The supergravity devices used in the present invention are all prior art, such as Figure 1 As shown in , the supergravity reactor comprises a motor 1, a housing 2, a rotor 3, and a liquid distributor 4. The output shaft of the motor 1 passes through the rotor in the fixed rotating disk in the upper housing 2, and the discharge port is at the bottom of the housing.
[0045] S4, active component loading by impregnation method:
[0046] The coated carrier is immersed in a prepared metal salt solution containing active components and allowed to stand for a period of time to obtain a monolithic catalyst precursor; it is then dried at room temperature, then dried in a vacuum drying oven, and finally placed in a tubular furnace for reduction in a hydrogen environment to obtain a monolithic catalyst.
[0047] According to some embodiments of the present invention, in step S1, the carrier of the monolithic catalyst includes one of cordierite, nickel foam, copper foam, aluminum foam or alloy foam.
[0048] According to some embodiments of the present invention, the ultrasonic cleaning is performed 1-3 times; and the deionized water rinsing is performed 3-5 times.
[0049] According to some embodiments of the present invention, in step S1, the ultrasonic cleaning time is 10-30 min / time; and the deionized water rinsing time is 5-10 min / time.
[0050] According to some embodiments of the present invention, in step S1, the time for soaking the carrier in the HCl solution is 25-35 minutes.
[0051] According to some embodiments of the present invention, in step S1, the drying time at room temperature is 5-12 hours.
[0052] According to some embodiments of the present invention, in step S1, the drying temperature in the oven is 30-80° C. and the drying time is 2-5 hours.
[0053] According to some embodiments of the present invention, in step S1, the calcination temperature in the muffle furnace is 200-700° C., and the calcination time is 1.5-3 h.
[0054] According to some embodiments of the present invention, in step S1, the concentration of the HCl solution is 0.5-5 mol / L; more preferably, the concentration of the HCl solution is 3-4 mol / L.
[0055] According to some embodiments of the present invention, in step S2, the coating comprises one of silicon oxide, aluminum oxide, cerium oxide, activated carbon, and molecular sieve.
[0056] According to some embodiments of the present invention, in step S3, the rotation speed of the rotor in the ultragravity reactor is 500-1500 r / min; preferably, in step S3, the cyclic reaction for a period of time refers to a cyclic reaction for 40-60 min.
[0057] According to some embodiments of the present invention, in step S3, the coated carrier is taken out and dried at room temperature for 10-14 hours; the temperature in the oven is 70-90° C., and the drying time in the oven is 1-3 hours.
[0058] According to some embodiments of the present invention, in step S3, the calcination temperature in the tube furnace is 450-550° C., the calcination time is 1-3 h, and the heating rate is 4-6° C. / min.
[0059] According to some embodiments of the present invention, in step S4, the metal salt solution includes one or more of palladium salts, platinum salts, cobalt salts, nickel salts, copper salts, and iron salts.
[0060] According to some embodiments of the present invention, in step S4, the standing for a period of time refers to standing for 20-60 minutes.
[0061] According to some embodiments of the present invention, in step S4, the drying time at room temperature is 10-14 hours, and the drying temperature in the vacuum drying oven is 55-65° C. and the drying time is 4-6 hours.
[0062] According to some embodiments of the present invention, in step S4, the temperature in the tube furnace is 380-420° C., the reduction time is 1.5-2.5 h, and the heating rate is 1.5-2.5° C. / min.
[0063] Example 1
[0064] A method for preparing a monolithic catalyst using a high gravity reactor comprises the following steps:
[0065] 1) Surface pretreatment of nickel foam carrier:
[0066] The nickel foam carrier was cut into cylinders by wire cutting. The nickel foam carrier was respectively placed in acetone, alcohol, and deionized water and cleaned with ultrasonic waves for 10 min and repeated 3 times. Then, the catalyst substrate was immersed in a 0.5 mol / L HCl solution for 30 min, taken out and rinsed with deionized water 3 times to ensure that the residual solution in the pores was blown clean. The substrate was dried at room temperature for 12 h, dried in an oven for 5 h, and then calcined in a muffle furnace at 300 °C for 1 h.
[0067] 2) Prepare SiO2 sol, a coating slurry, for forming a coating:
[0068] Add deionized water, anhydrous ethanol and ammonia water into a three-necked flask, start stirring in a constant temperature water bath, and then quickly add tetraethyl orthosilicate into the above three-necked flask. The volume ratio of deionized water, anhydrous ethanol, ammonia water and tetraethyl orthosilicate is 8:12:1:1. Continue stirring at 35°C for 2h. Stop the reaction after the solution gradually turns milky white. The reaction solution is aged at room temperature for 24h to obtain SiO2 sol;
[0069] 3) The treated nickel foam is loaded into the rotor of the supergravity reactor, and the SiO2 sol obtained in step S2 is introduced into the supergravity reactor under supergravity environment, the motor 1 and the centrifugal pump are turned on, and the speed of the supergravity reactor is adjusted to 1500r / min. The SiO2 sol is transported to the liquid distributor 4 through the centrifugal pump, and sprayed into the rotor 3 through the spray hole, and then returned to the liquid storage tank after passing through the rotor, and the cycle reaction is 60min; the nickel foam loaded with SiO2 coating is first dried at room temperature for 12h, then dried in an oven at 80°C for 2h, and finally placed in a tubular furnace and roasted at 500°C for 2h (heating rate: 5°C / min);
[0070] 4) Loading active components by impregnation method
[0071] Dissolve PdCl2 in deionized water, add dilute HCl and heat at 60°C for 3 hours. Immerse the nickel foam with SiO2 coating in the above solution and let it stand for a while to obtain the precursor of the monolithic catalyst. Then dry it at room temperature for 12 hours, then dry it in a vacuum drying oven at 60°C for 5 hours, and finally put it in a tubular furnace and reduce it at 400°C (heating rate: 2°C / min) in a hydrogen environment for 2 hours to obtain a monolithic catalyst.
[0072] The structural data and performance data of the monolithic catalyst obtained in this example are shown in Tables 1 and 2 below.
[0073] Example 2
[0074] A method for preparing a high-strength monolithic catalyst using a supergravity reactor comprises the following steps:
[0075] 1) Surface pretreatment of nickel foam carrier:
[0076] The nickel foam carrier was cut into cylinders by wire cutting; the nickel foam carrier was respectively placed in acetone, alcohol, and deionized water and ultrasonically cleaned for 30 minutes and repeated 3 times, and then the catalyst substrate was immersed in a 4 mol / L HCl solution for 30 minutes, and then taken out and rinsed with deionized water 3 times to ensure that the residual solution in the pores was blown clean, dried at room temperature for 12 hours, dried in an oven for 5 hours, and then placed in a muffle furnace for calcination at 400°C for 2 hours;
[0077] 2) Prepare SiO2 sol, a coating slurry, for forming a coating:
[0078] Add deionized water, anhydrous ethanol and ammonia water into a three-necked flask, start stirring in a constant temperature water bath, and then quickly add tetraethyl orthosilicate into the above three-necked flask. The volume ratio of deionized water, anhydrous ethanol, ammonia water and tetraethyl orthosilicate is 10:12:1:1. Continue stirring at 45°C for 2h. Stop the reaction after the solution gradually turns milky white. The reaction solution is aged at room temperature for 24h to obtain SiO2 sol.
[0079] 3) Load the treated nickel foam into the rotor of the supergravity reactor, pass the SiO2 sol obtained in step S2 into the supergravity reactor under supergravity, start the motor 1 and the centrifugal pump, adjust the speed of the supergravity reactor to 1500r / min, and transport the reaction liquid to the liquid distributor 4 through the centrifugal pump, spray it into the rotor 3 through the injection hole, and return to the liquid storage tank after passing through the rotor, and circulate the reaction for 60min. The nickel foam loaded with SiO2 coating is first dried at room temperature for 12h, then dried in an oven at 80℃ for 2h, and finally placed in a tubular furnace and roasted at 500℃ for 2h (heating rate: 5℃ / min);
[0080] 4) Loading active components by impregnation method
[0081] Dissolve PdCl2 in deionized water, add dilute HCl and heat at 60°C for 3 hours. Immerse the nickel foam with SiO2 coating in the above solution and let it stand for a while to obtain the precursor of the monolithic catalyst; then dry it at room temperature for 12 hours, then dry it in a vacuum drying oven at 60°C for 5 hours, and finally put it in a tubular furnace and reduce it at 400°C (heating rate: 2°C / min) in a hydrogen environment for 2 hours. The monolithic catalyst is obtained.
[0082] The structural data and performance data of the monolithic catalyst obtained in this example are shown in Tables 1 and 2 below.
[0083] Comparative Example 1
[0084] A method for preparing a monolithic catalyst by impregnation method comprises the following steps:
[0085] 1) Surface pretreatment of nickel foam carrier:
[0086] The nickel foam carrier was cut into cylinders by wire cutting. The nickel foam carrier was placed in acetone, alcohol, and deionized water and cleaned with ultrasonic waves for 30 minutes, and then the catalyst substrate was soaked in 4 mol / L HCl solution for 30 minutes. After being taken out, it was rinsed with deionized water for 3 times to ensure that the residual solution in the pores was purged clean, dried at room temperature for 12 hours, dried in an oven for 5 hours, and then placed in a muffle furnace at 400°C for 2 hours.
[0087] 2) Prepare SiO2 sol, a coating slurry, for forming a coating:
[0088] Add deionized water, anhydrous ethanol and ammonia water into a three-necked flask, start stirring in a constant temperature water bath, and then quickly add tetraethyl orthosilicate into the above three-necked flask. The volume ratio of deionized water, anhydrous ethanol, ammonia water and tetraethyl orthosilicate is 10:12:1:1. Continue stirring at 45°C for 2h. Stop the reaction after the solution gradually turns milky white. Let the reaction solution stand at room temperature for 24h to obtain SiO2 sol;
[0089] 3) The treated nickel foam was statically immersed in a beaker containing SiO2 sol for 60 minutes. The nickel foam loaded with SiO2 coating was first dried at room temperature for 12 hours, then dried in an oven at 80°C for 2 hours, and finally placed in a tube furnace and calcined at 500°C for 2 hours (heating rate: 5°C / min);
[0090] 4) Loading active components by impregnation method:
[0091] Dissolve PdCl2 in deionized water, add dilute HCl and heat at 60°C for 3 hours. Immerse the nickel foam with SiO2 coating in the above solution and let it stand for a while to obtain the precursor of the monolithic catalyst. Then dry it at room temperature for 12 hours, then dry it in a vacuum drying oven at 60°C for 5 hours, and finally put it in a tubular furnace and reduce it at 400°C (heating rate: 2°C / min) in a hydrogen environment for 2 hours to obtain a monolithic catalyst.
[0092] The structural data and performance data of the monolithic catalyst obtained in this comparative example are shown in Tables 1 and 2 below.
[0093] It can be seen from the data of this comparative example and Table 1 and Table 2 that the SiO2 coating loaded on the surface of nickel foam by an ultra-gravity reactor has higher adhesion to mechanical stress than the coating loaded by the traditional impregnation method, and the shedding rate of the coating and active components is significantly reduced.
[0094] Comparative Example 2
[0095] A method for preparing a monolithic catalyst by a slurry circulation method comprises the following steps:
[0096] 1) Surface pretreatment of nickel foam carrier:
[0097] The nickel foam carrier was cut into cylinders by wire cutting. The nickel foam carrier was placed in acetone, alcohol, and deionized water and cleaned with ultrasonic waves for 30 minutes, and then the catalyst substrate was soaked in 4 mol / L HCl solution for 30 minutes. After being taken out, it was rinsed with deionized water for 3 times to ensure that the residual solution in the pores was purged clean, dried at room temperature for 12 hours, dried in an oven for 5 hours, and then placed in a muffle furnace at 400°C for 2 hours.
[0098] 2) Prepare SiO2 sol, a coating slurry, for forming a coating:
[0099] Add deionized water, anhydrous ethanol and ammonia water into a three-necked flask, start stirring in a constant temperature water bath, and then quickly add tetraethyl orthosilicate into the above three-necked flask. The volume ratio of deionized water, anhydrous ethanol, ammonia water and tetraethyl orthosilicate is 10:12:1:1. Continue stirring at 45°C for 2h. Stop the reaction after the solution gradually turns milky white. The reaction solution is aged at room temperature for 24h to obtain SiO2 sol.
[0100] 3) The nickel foam is fixed in a plastic tube with an inner diameter of 3.8 mm. The SiO2 sol is pumped into the plastic tube filled with nickel foam by a peristaltic pump and circulated for 30 minutes. The flow rate of the SiO2 sol is controlled to be 162 ml / min. The nickel foam is then kept in a tube without SiO2 sol environment circulation (air circulation) for 10 minutes. The nickel foam loaded with SiO2 coating is first dried at room temperature for 12 hours, then dried in an oven at 80°C for 2 hours, and finally placed in a tubular furnace and calcined at 500°C for 2 hours (heating rate: 5°C / min);
[0101] 4) Loading active components by impregnation method:
[0102] Dissolve PdCl2 in deionized water, add dilute HCl and heat at 60°C for 3 hours. Immerse the nickel foam with SiO2 coating in the above solution and let it stand for a while to obtain the precursor of the monolithic catalyst. Then dry it at room temperature for 12 hours, then dry it in a vacuum drying oven at 60°C for 5 hours, and finally put it in a tubular furnace and reduce it at 400°C (heating rate: 2°C / min) in a hydrogen environment for 2 hours to obtain the monolithic catalyst.
[0103] It can be seen from the data of this comparative example and Table 1 and Table 2 that the SiO2 coating loaded on the surface of nickel foam by the ultra-gravity reactor has higher adhesion to mechanical stress than the coating loaded by the slurry circulation method, and the shedding rate of the coating and active components is significantly reduced.
[0104] The structural parameters of Example 1, Example 2, Comparative Example 1 and Comparative Example 2 are shown in Table 1 below. The above-prepared monolithic catalyst was subjected to ultrasonic vibration and thermal shock experiments to test the shedding rate of the coating and active components. The results are shown in Table 2 below.
[0105] Table 1: Structural parameters of monolithic catalysts
[0106] Example 1 Example 2 Comparative Example 1 Comparative Example 2 <![CDATA[SiO2 coating loading: g / g]]> 0.0189 0.0173 0.0275 0.0217 <![CDATA[Specific surface area: m 2 / g]]> 27.2 34.7 21.7 20.1
[0107] Note: The loading amount of SiO2 coating is the ratio of the actual loading mass of SiO2 to the mass of nickel foam.
[0108] Table 2: The shedding rate of coating and active components in the ultrasonic vibration and thermal shock test of monolithic catalyst
[0109]
[0110]
[0111] Note: (1) Ultrasonic vibration experiment: The monolithic catalyst was placed in deionized water and ultrasonicated in an ultrasonic cleaner with an operating frequency of 40 kHz and a power of 135 W for 30 min. The shedding rates of the coating and active components were calculated.
[0112] (2) Thermal shock test: The sample was placed in a tubular furnace and calcined at 500 °C for 1 h (heating rate 10 °C / min), then quickly placed in cold water for cooling, and dried at 80 °C for 2 h before calculating the shedding rate.
[0113] The formula for calculating the shedding rate is as follows:
[0114]
[0115] Example 3
[0116] Example 1 is repeated, except that: in step S1, the carrier is one of cordierite, foamed copper, foamed aluminum or foamed alloy;
[0117] After testing, the monolithic catalyst coating and the shedding rate of active components obtained in this embodiment and in embodiment 1 are similar.
[0118] In summary, the present invention creates a centrifugal environment through an ultra-gravity reactor, and loads the SiO2 coating onto the carrier under the action of centrifugal force, which is beneficial to the bite effect between the SiO2 coating and the carrier matrix, thereby enhancing the mechanical locking at the interface between the two, thereby improving the adhesion of the integral catalyst coating.
[0119] Obviously, the above embodiments of the present invention are merely examples for clearly explaining the present invention, and are not intended to limit the implementation methods of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is impossible to list all implementation methods here. Any obvious changes or modifications derived from the technical solution of the present invention are still within the scope of protection of the present invention.
Claims
1. A method for preparing a monolithic catalyst using a high gravity reactor, characterized in that: The steps include: S1. Carrier surface acid etching pretreatment: The carrier of the monolithic catalyst is immersed in acetone, alcohol, and deionized water respectively and cleaned with ultrasonic wave, and then the carrier is immersed in HCl solution, taken out and rinsed with deionized water to ensure that the residual solution in the pores is blown clean, dried at room temperature, dried in an oven, and calcined in a muffle furnace; S2, preparing a coating slurry for forming a coating, wherein the coating slurry is SiO2 sol; S3, loading the carrier treated in step S1 into the rotor of the supergravity reactor, passing the coating slurry obtained in step S2 into the supergravity reactor under supergravity environment, turning on the motor and the centrifugal pump, conveying the coating slurry to the liquid distributor of the supergravity reactor through the centrifugal pump, spraying it into the rotor through the spray hole, returning to the liquid storage tank after passing through the rotor, and circulating the reaction for a period of time; taking out the carrier loaded with the coating, first drying it at room temperature, then drying it in an oven, and finally placing it in a tubular furnace for calcination; obtaining a carrier of a monolithic catalyst with a coating; S4, active component loading by impregnation method: The coated carrier is immersed in a prepared metal salt solution containing active components and allowed to stand for a period of time to obtain a monolithic catalyst precursor; it is then dried at room temperature, then dried in a vacuum drying oven, and finally placed in a tubular furnace for reduction in a hydrogen environment to obtain a monolithic catalyst.
2. The method for preparing a monolithic catalyst using a high gravity reactor according to claim 1, characterized in that: In step S1, the carrier of the monolithic catalyst includes one of cordierite, nickel foam, copper foam, aluminum foam or alloy foam.
3. The method for preparing a monolithic catalyst using a high gravity reactor according to claim 1, characterized in that: In step S1, the ultrasonic cleaning is performed 1-3 times; the deionized water washing is performed 3-5 times; In step S1, the ultrasonic cleaning time is 10-30 min / time; the deionized water rinsing time is 5-10 min / time; In step S1, the time for soaking the carrier in the HCl solution is 25-35 minutes; In step S1, the drying time at room temperature is 5-12 hours; In step S1, the drying temperature in the oven is 30-80°C and the drying time is 2-5h; In step S1, the calcination temperature in the muffle furnace is 200-700° C., and the calcination time is 1.5-3 h.
4. The method for preparing a monolithic catalyst using a high gravity reactor according to claim 1, characterized in that: In step S1, the concentration of the HCl solution is 0.5-5 mol / L.
5. The method for preparing a monolithic catalyst using a high gravity reactor according to claim 1, characterized in that: In step S3, the rotation speed of the rotor in the ultra-gravity reactor is 500-1500 r / min; In step S3, the cyclic reaction for a period of time refers to a cyclic reaction of 40-60 minutes; In step S3, the coated carrier is taken out and dried at room temperature for 10-14 hours; the temperature in the oven is 70-90° C., and the drying time in the oven is 1-3 hours; In step S3, the calcination temperature in the tube furnace is 450-550°C, the calcination time is 1-3h, and the heating rate is 4-6°C / min.
6. The method for preparing a monolithic catalyst using a high gravity reactor according to claim 1, characterized in that: In step S4, the metal salt includes one or more of palladium salt, platinum salt, cobalt salt, nickel salt, copper salt and iron salt.
7. The method for preparing a monolithic catalyst using a high gravity reactor according to claim 1, characterized in that: In step S4, the standing for a period of time refers to standing for 20-60 min.
8. The method for preparing a monolithic catalyst using a high gravity reactor according to claim 1, characterized in that: In step S4, the drying time at room temperature is 10-14 hours, and the drying temperature in the vacuum drying oven is 55-65°C for 4-6 hours.
9. The method for preparing a monolithic catalyst using a high gravity reactor according to claim 1, characterized in that: In step S4, the temperature in the tube furnace is 380-420°C, the reduction time is 1.5-2.5h, and the heating rate is 1.5-2.5°C / min.
Citation Information
Patent Citations
Method for hydrocracking polycyclic aromatic hydrocarbons in super gravity reactor
CN107653002A
Pd-based integral catalyst for catalytic combustion of exhaust gas of VOCs and preparation method of catalyst
CN108435163A
Apparatus and method for preparing metal catalyst
CN108854931A
Two-component manganese-based loaded catalyst prepared by using supergravity spray impregnation method and application of catalyst
CN110302797A
Method and device for degrading phenol wastewater by heterogeneous catalysis of ozone in high gravity field
CN110436603A
